2017
DOI: 10.1177/1075547017709792
|View full text |Cite
|
Sign up to set email alerts
|

Fear of the Fear of the Flu: Assumptions About Media Effects in the 2009 Pandemic

Abstract: In this article, we present a qualitative study of the Norwegian print news coverage of the 2009 pandemic. In initial research, we found fear to be a notable aspect of the coverage. In studying a relevant subsample in-depth, we discovered that, although there was no sound basis on which to make conclusions about what effects the coverage was having on the public, various actors—including media themselves—came on the mediated scene to express fears that it would create fear and panic. We argue that the mediatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 32 publications
0
15
0
3
Order By: Relevance
“…Public health organizations may consider shaping media coverage in such a way that it motivates appropriate public behavioral responses (Liu, Austin, Lee, Jin, & Kim, 2020). Instructions can be aimed at regular media (Bjørkdahl & Carlsen, 2017) as well as social media platforms (Guidry, Jin, Orr, Messner, & Meganck, 2017;Guzmán Do Nascimento, 2018). This requires an understanding of the pros and cons of different platforms and knowledge about the role of news media and comments on Facebook (Rodin, Ghersetti, & Oden, 2019), YouTube (Tang, Bie, Park, & Zhi, 2018), Twitter, and Instagram (Guidry et al, 2017).…”
Section: Domain V: Instructions To the Publicmentioning
confidence: 99%
“…Public health organizations may consider shaping media coverage in such a way that it motivates appropriate public behavioral responses (Liu, Austin, Lee, Jin, & Kim, 2020). Instructions can be aimed at regular media (Bjørkdahl & Carlsen, 2017) as well as social media platforms (Guidry, Jin, Orr, Messner, & Meganck, 2017;Guzmán Do Nascimento, 2018). This requires an understanding of the pros and cons of different platforms and knowledge about the role of news media and comments on Facebook (Rodin, Ghersetti, & Oden, 2019), YouTube (Tang, Bie, Park, & Zhi, 2018), Twitter, and Instagram (Guidry et al, 2017).…”
Section: Domain V: Instructions To the Publicmentioning
confidence: 99%
“…There is some previous work on macro-level factors that might explain why some countries are more resilient to false information about politics (see, e.g., Humprecht, Esser, and Van Aelst, 2020). The effects of news and social media on peoples' understanding of rare virus outbreaks deserve further research: these range from underreaction to inducing panic (Fu and Zhu, 2020;Bjørkdahl and Carlsen, 2017;Klemm, Das, and Hartmann, 2016;Kilgo, Yoo, and Johnson, 2019). While audiences across the world were exposed to false claims about COVID-19 during the first three months of the pandemic, surveys indicated that many people recognised or ignored these (Ofcom, 2020;Cushion, Kyriakidou, Morani, and Soo, 2020;Nielsen, Fletcher, Newman, Brennen, and Howard, 2020).…”
Section: Methodological Considerations: Focusing On Potential Harmmentioning
confidence: 99%
“…Why? Because the press is not making a splash out of the annual flu story (Bjorkdahl and Carlsen, 2017). So, on the one hand, one must remember that, in fact, coronavirus does not pose a more serious threat than the "ordinary" flu, but, on the other, this is not a reason to neglect prevention (Zhang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%